Selection and Characterization of an α6β4 Integrin blocking DNA Aptamer - Katharina Berg; Tobias Lange; Florian Mittelberger; Udo Schumacher; Ulrich Hahn (Molecular Therapy: Nucleic Acids, 2016)
The heterodimeric laminin receptor α6β4 integrin plays a central role in the promotion of tumor cell growth, invasion, and organotropic metastasis. As an overproduction of the integrin is often linked to a poor prognosis, the inhibition of integrin α6β4 binding to laminin is of high therapeutical interest. Here, we report on the combination of a cell-systematic evolution of ligands by exponential enrichment and a bead-based selection resulting in the first aptamer inhibiting the interaction between α6β4 integrin and laminin-332. This Integrin α6β4-specific DNA Aptamer (IDA) inhibits the adhesion of prostate cancer cells (PC-3) to laminin-332 with an IC50 value of 149 nmol/l. The Kd value concerning the aptamer's interaction with PC-3 cells amounts to 137 nmol/l. Further characterization showed specificity to α6 integrins and a half-life in murine blood plasma of 6 hours. Two truncated versions of the aptamer retained their binding capacity, but lost their ability to inhibit the interaction between laminin-332 and PC-3 cells. Confocal laser scanning microscope studies revealed that the aptamer was internalized into PC-3-cells. Therefore, in addition to the adhesion-blocking function of this aptamer, IDA could also be applied for the delivery of siRNA, microRNA or toxins to cancer cells presenting the integrin α6β4.